PENGARUH INOVASI DAN KREATIVITAS WIRAUSAHA TERHADAP KEBERHASILAN USAHA KECIL MENENGAH PADA PENJAHIT PAKAIAN DI KECAMATAN BATURAJA TIMUR KABUPATEN OKU - Darman Syafei; Jalaludin Jalaludin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
ABSTRACT The analytical method used is a quantitative method using Multiple Linear Regression analysis tool that uses validity and reliability tests, as well as the T test and F test. The results of this study are explaining the value of t Innovation (X1) of 3.090 is higher than the t table of 2.07387 which means that the Innovation variable has a significant influence on Business Success, and t value Entrepreneurial Creativity (X2) of 6.146 is higher than t table of 2.07387 which means that the variable Entrepreneurial Creativity has a significant influence on Business Success. Simultaneous testing (F Test) of Entrepreneurial Innovation and Creativity variable show an arithmetic of 75.119 which is higher than the f table of 3.44, it means that simultaneously the Entrepreneurial Innovation and Creativity influence signficantly on the Success of Small and Medium Enterprises in Clothing Tailors in East Baturaja Sub-District. The (R Square) which is 0.872 means that the contribution of Entrepreneurial Innovation and Creativity is 87.2% and the remaining 12.8% is influenced by other variables not examined in this study such as opportunity and HR factors.